Transition Metal Dichalcogenides/Gold-Based Surface Plasmon Resonance Sensors: Exploring the Geometrical and Material Parameters - Varasteanu, Pericle (Plasmonics (Norwell, Mass.), 2020)
In this study, we explored the geometrical and material parameters of surface plasmon resonance (SPR) sensors, in order to gain insight about the mechanisms that control the sensors’ response when different 2D materials monolayers (MoS 2 , MoSe 2 , WS 2 , WSe 2 ) are used to modify the surface. Accordingly, the surface plasmons’ (SPs) dispersion relations, the reflectivity maps and both reflectivity and phase responses for the visible and near-infrared wavelengths range (400–1400 nm), were systematically investigated by using COMSOL Multiphysics (RF Module) and transfer matrix method (TMM) algorithm considering a modified Kretschmann configuration. We showed that the sensitivity of the modified structures is enhanced for wavelengths between 600 and 1000 nm both in reflectivity and phase. By evaluating also the influence of the number of 2D material monolayers, the highest sensitivity in reflectivity was obtained at 700 nm when five monolayers of MoS 2 were added, reaching 220 deg/RIU for a change in dielectric’s refractive index of 0.002 RIU, which is 45% higher than that of the standard bare structure. Regarding the phase response, it was shown that by adding only one monolayer of MoS 2 , a sensitivity of 9 × 10 5 deg/RIU is achieved for a refractive index change of 10 −6 RIU.